Community-Based Agro-Silvopastoral Systems: Integrating Forestry, Agriculture, and Livestock for Sustainable Rural Development in Forest Regions - Sunariyo, Sunariyo; Firdausi, Rizal Zubad (SERUNAI, 2024)
This study explored the implementation and impact of community-based agro-silvopastoral systems integrating forestry, agriculture, and livestock to promote sustainable rural development in forest regions. The program achieved significant milestones through multi-stakeholder coordination, including partnerships with local government and active community engagement. The collaboration facilitated the development of tailored maintenance and production procedures, enhancing local understanding and acceptance of sustainable agro-silvopastoral practices. Key findings highlight the success of operational support initiatives, such as financial and technical assistance, which enabled farmers to adopt and sustain agro-silvopastoral practices. Additionally, enterprise support initiatives, including training and resource access, bolstered the development of diversified agroforestry enterprises, contributing to economic resilience and improved livelihoods. Continuous mentorship and guidance empowered community members with the knowledge and skills needed for sustainable management and expansion of agro-silvopastoral systems. Overall, the program's comprehensive and participatory approach significantly enhanced sustainability, economic resilience, and environmental stewardship in rural communities.